Solve the system of equations by substitution and
explain all your steps in words:
3x + y = 12
x = y − 8 .
Is this a good way to explain this problem?
Step 1: Since X is given to us. We can plug it into the x-value in the first equation. x= y-8 into 3x+y=12
3(y-8)=12. Distribute to solve for your new equation.
3y-24=12. Add 24 to both sides to get 3y by itself.
3y=36. Divide by 3
3y/3=36/3. Y=12.
I have never seen a math problem like this. Its always been have the equation or whatever. Solve for blah blah
2 answers
what happened to the y that was already in the 1st equation?
oh snaps I left it out. It should be 3y-24+y=12 should turn into 4y-24=12. its still 36=4y
y=9 now. Thanks Scott
y=9 now. Thanks Scott